Pengaruh Motivasi Dan Kemampuan Terhadap Kinerja Anggota Dewan Perwakilan Rakyat Daerah Kabupaten Bangka - Zamhari - -; Darwati - Susilastuti; Ahmad - Yani (Jurnal Media Wahana Ekonomika, 2017)
The purpose of this study was to analyze the influence of motivation and the ability simultaneously to the performance of Members of Parliament Bangka Regency and to analyze the influence of motivation on the performance of Members of the House of Representatives District Bangka and to analyze the ability of members of the House of Representatives District Bangka. The samples used were as many as all board members drawn from the population of 30. Instrument of research using questionnaires, which are arranged in a scale of 1-5, score 1 for very poor response and score 5 for a very good response. Data analysis techniques used were test validity, test reliability and testing hypotheses. Motivation of board members supported primarily by the high council members the opportunity to develop your own potential in work, and reflected the ability of intellectual ability, physical ability. While performance can be seen from the productivity, quality of service, responsibility, responsi-veness and akutanbilitas. The results showed that motivation and the ability of parliaments Bangka Regency either jointly or partial influence significant effect on performance. Key words : motivation, ability and performance